Prediction of Hematoma Expansion in Patients With Intracerebral Hemorrhage Using Thromboelastography With Platelet Mapping: A Prospective Observational Study - He, Qiuguang; Zhou, You; Liu, Chang; Chen, Zhongqiu; Wen, Rong; Wu, Yue; Xie, Zongyi; Cheng, Yuan; Cheng, Si (Frontiers in Neurology, 2021)
Background and Purpose: The purpose of the study was to evaluate the usefulness of thrombelastography with platelet mapping (TEG-PM) for predicting hematoma expansion (HE) and poor functional outcome in patients with intracerebral hemorrhage (ICH). Methods: Patients with primary ICH who underwent baseline computed tomographic (CT) and TEG-PM within 6 hours after symptom onset were enrolled in the observational cohort study. We performed univariate and multivariate logistic regression models to assess the association of admission platelet function with HE and functional outcome. In addition, receiver operating characteristic (ROC) curve analysis investigated the accuracy of platelet function in predicting HE. Mediation analysis was undertaken to determine causal associations among platelet function, HE, and outcome. Results: Of 142 patients, 37 (26.1%) suffered HE. Multivariate logistic regression identified arachidonic acid (AA) (P=0.002) and adenosine diphosphate (ADP) inhibition (P=0.008) as significant independent predictors of HE. The area under the ROC curves was 0.727 for AA inhibition and 0.721 for ADP inhibition. Optimal threshold for AA inhibition was 41.75% (75.7% sensitivity, 67.6% specificity) and ADP inhibition was 65.8% (73.0% sensitivity, 66.7% specificity). AA (P=0.006) and ADP (P=0.010) inhibition were also associated with worse 3-month outcomes after adjusting for age, admission Glasgow Coma Scale score, intraventricular hemorrhage, baseline hematoma volume and hemoglobin. Mediation analysis showed that the effect of higher platelet inhibition with poor outcomes was mediated through HE. Conclusions: These findings suggest that the reduced platelet response to ADP and AA independently predict HE and poor outcome in patients with ICH. Platelet function may represent a modifiable target of ICH treatment.